Da‘wah Activities of Jamā‘ah Masturah in Aceh Besar - Mira Fauziah (Program Doktor Akidah dan Filsafat Islam, 2020)
Jamā‘ah mastūrah is jamā‘ah tablīgh women who take part in da‘wah activities. jamā‘ah mastūrah has different propaganda methods from the usual by the dāi (preacher man) and dā’iyah (female preachers) in general who preached in front of an audience. The method of preaching the jamā‘ah mastūrah is fardiyah, which is individual preaching to other women. This study aims to understand the roles of jamā‘ah mastūrah in preaching activities in Aceh Besar and how their da‘wah (athar) tothe community is the object of da‘wah (mad‘ū). This article results from field research conducted at three locations: Gampong Luthu, Gampong Cot Goh, and Gampong Neuheun in Aceh Besar. Data collection was through interviews and documentation studies. The findings are twofold: first, jamā‘ah mastūrah role as da‘I well in conveying Islam to fellow women. The material of the da‘wah they convey is mainly related to orders to cover the awrat, abandon bad behavior, and invite them to attend recitation (ta‘lim mastūrah); second, the effect of da‘wah (athar) takes a relatively long time.